How to address vaccine hesitancy? Lessons from National Hepatitis B Immunization Program in China - Jiang, Haiting; Wei, Chengyu (Frontiers in Public Health, 2024)
China, with the severe burden of Hepatitis B, plays a significant role in the global efforts towards eliminating hepatitis B disease by 2030. Vaccination is recognized as the most effective measure to prevent infectious diseases. However, vaccine hesitancy remains a significant barrier to achieving herd immunity across diverse populations. To address this issue, the health ministries and public health authorities in China have implemented various measures to encourage hepatitis B vaccination.China's National Hepatitis B Immunization Program, initiated in 1985, has been successful in controlling this vaccine-preventable disease. Given the challenges in eliminating hepatitis B, strengthening the National Hepatitis Immunization Program in China is of utmost importance.Through an analysis of policy documents, reports, and scientific papers, the history of the program was summarized, and effective approaches to address vaccine hesitancy were identified. This will help achieve universal health coverage of vaccines and effectively work towards meeting the goals set for 2030.